Estratégia de feedback no desenvolvimento de habilidades investigativas de estudantes universitários - Huauya Quispe, Pedro (2021)
Its objective is to analyze the incidences of the feedback strategy in the development of investigative skills of students of primary and secondary education of the Faculty of Education Sciences, 2019; level of explanatory research of pre-experimental design with pre and post-test, the sample consisted of 39 students from primary and secondary education, the data was collected through the survey technique and pedagogical test; The hypothesis test was carried out through Student's t for related samples with a confidence level of 95%. It is concluded that at 95% confidence level, the feedback strategy significantly affects the development of investigative skills of students of primary and secondary education of the Faculty of Education Sciences, 2019 (0.000 <0.05).